Inclusive and differential cross section measurements of single top quark production in association with a Z boson in proton-proton collisions at √s = 13 TeV - KAYA, MİTHAT (My University, 2022)
© 2022, The Author(s).Inclusive and differential cross sections of single top quark production in association with a Z boson are measured in proton-proton collisions at a center-of-mass energy of 13 TeV with a data sample corresponding to an integrated luminosity of 138 fb−1 recorded by the CMS experiment. Events are selected based on the presence of three leptons, electrons or muons, associated with leptonic Z boson and top quark decays. The measurement yields an inclusive cross section of 87.9−7.3+7.5(stat)−6.0+7.3(syst) fb for a dilepton invariant mass greater than 30 GeV, in agreement with standard model (SM) calculations and represents the most precise determination to date. The ratio between the cross sections for the top quark and the top antiquark production in association with a Z boson is measured as 2.37−0.42+0.56(stat)−0.13+0.27(syst). Differential measurements at parton and particle levels are performed for the first time. Several kinematic observables are considered to study the modeling of the process. Results are compared to theoretical predictions with different assumptions on the source of the initial-state b quark and found to be in agreement, within the uncertainties. Additionally, the spin asymmetry, which is sensitive to the top quark polarization, is determined from the differential distribution of the polarization angle at parton level to be 0.54 ± 0.16 (stat) ± 0.06 (syst), in agreement with SM predictions. [Figure not available: see fulltext.]
Keywords: Fizik; Temel Bilimler; Physics; Natural Sciences; Temel Bilimler (SCI); FİZİK, NÜKLEER; Natural Sciences (SCI); PHYSICS; PHYSICS, NUCLEAR; Nükleer ve Yüksek Enerji Fiziği; Fizik Bilimleri; Nuclear and High Energy Physics; Physical Sciences; Hadron-Hadron Scattering; Top Physics